A exploração romana do mármore na Quinta de Santo Adrião, Vimioso / Miranda do Douro - Martins, Carla Maria Braz (2019)
The aim of this work is to document the exploration of marble in Roman times in Santo Adrião, Vimioso in the municipality of Miranda do Douro, based on the analysis of materials collected there at the opening of the quarry in the late nineteenth century. The materials were classified and studied according to their functionality, especially working instruments, processed products and semi-manufactures and an ornament object.